Glottal Waveforms in Normals - R, Sridhara (Journal of All India Institute of Speech and Hearing)
The production of voice is highly complex. Thorough understanding of the physiology of voice production needs proper measurement techniques. Abnormal oscillatory movements of vocal cords are known lo manifest in the form of phonatory disorder. The measurement and analysis of the vibratory pattern of vocal fold has the potential to provide detailed information on the patho-physiology of the vocal fold during phonation.